Criminal Responsibility For Criminal Followers Producing And Selling "Drinks" White Alcohol / White Liquor In The Legal Area Of Kudus Police - Hendro Santiko; Akhmad Khisni (Jurnal Daulat Hukum, 2020)
This research wants to answer the problem. How is law enforcement against criminal offenders producing and selling "White Alcohol/ White Liquor" in the Kudus police area? and criminal liability against criminal offenders producing and selling "White Alcohol/ White Liquor" in the area of the Kudus Police District and in the future?Based on the results of the study concluded that 2 (two) methods of law enforcement on the circulation of alcohol by the Kudus Police District, namely preventive and repressive.Criminal accountability against criminal offenders producing and selling "White Alcohol/ White Liquor" in the area of the Kudus Police in eradicating opaque liquor in the Kudus Police Region, Obstacles faced by the Kudus Police Sabhara Unit are relating to the limited number of members of the Kudus Police Sabhara unit that generally still unsatisfactory, not yet maximized and the evenly distributed socialization steps of the Regional Government Regulation carried out at the community level, so far it is not uncommon for insufficient understanding of procedures or systems at the time of preparation up to the enactment of Perda Sabhara Unit of the Kudus Police Unit in eradicating liquor oplosan in the Kudus Police District Region,criminal liability against criminal offenders producing and selling "White Alcohol/ White Liquor" that will come in the renewal of Indonesian criminal is done by providing guidance, advising or guiding so as not to repeat the mistakes that have been made namely violating local regulations.Keywords: Criminal Liability; Criminals; Producing and Selling White Alcohol/ White Liquor.